ANALISIS SUPERVISI KLINIS KEPALA SEKOLAH DI SEKOLAH MENENGAH PERTAMA ISLAM TERPADU PONDOK PESANTREN RAUDHATUL ULUM SAKATIGA INDRALAYA OGAN ILIR - Sefri Kandi Ja'far Yazid (Raudhah - Proud To Be Professional, 2019)
This journal is entitled "Analysis of the Competency Analysis of the Principal's Clinical Supervision in Islamic Middle School Integrated Islamic Boarding School Raudhatul Ulum Sakatiga Indralaya Ogan Ilir". The main concern of education supervision is the problem of teaching quality and improvement efforts, and refers to the main mission of educational organizations, namely activities aimed at improving and improving academic quality. In other words, educational supervision is an activity that deals with the improvement, improvement of the process and learning outcomes. In the implementation of supervision at Raudhatul Ulum Sakatiga Middle School, the headmaster has conducted supervision activities, despite the assumption from teachers that the supervision activities are carried out to look for mistakes, but actually contain more coaching elements, so that the working conditions that are being supervised can be known for their shortcomings (not solely its error) to be told which part needs to be fixed. And become a tool for teachers to become more professional in teaching. The data source in this study consisted of primary data sources (school principals, curriculum chiefs and Raudhatul Ulum Junior High School IT teachers) and secondary data sources namely all supporting documents and data. Data collection techniques used are observation, documentation and interviews. While the data analysis technique used is descriptive qualitative by means of data reduction (summarizing and selecting the main points), data display (presenting data in a brief pattern), data verification (drawing conclusions temporarily). The research results obtained as follows: Supervision competencies conducted at Raudhatul Ulum Sakatiga Middle School IT have run well in accordance with the objectives. Supervision competencies in accordance with the principles, techniques, approaches and follow-up from the results of supervision conducted